2020
DOI: 10.3324/haematol.2019.241513
|View full text |Cite
|
Sign up to set email alerts
|

Elotuzumab, lenalidomide, and dexamethasone as salvage therapy for patients with multiple myeloma: Italian, multicenter, retrospective clinical experience with 300 cases outside of controlled clinical trials

Abstract: * Patients harboring a t(4;14), t(14;16), or del(17p) were classified as having high-risk disease and all other cases as being at standard risk. ONLINE SUPPLEMENTARY CONTENTS Elotuzumab, lenalidomide, and dexamethasone as salvage therapy for patients with multiple myeloma: Italian, multicenter, retrospective clinical experience with 300 cases outside of controlled clinical trials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 15 publications
6
22
1
Order By: Relevance
“…A graft vs. myeloma effect has been shown by the differences in post-allogeneic stem cell transplant relapse rates based on the inherited repertoire of KIR genes expressed by donor NK cells, indicating a role for NK cell-mediated suppression of relapse [22,24]. Lastly, NK cells mediate ADCC against myeloma cells in vitro and in vivo, thus enhancing the anti-MM activity of current therapies, which includes mAbs such as the anti-CD38 daratumumab and isatuximab [45] and the anti-SLAMF7 elotuzumab (Figure 2) [70,71].…”
Section: Nkmentioning
confidence: 99%
“…A graft vs. myeloma effect has been shown by the differences in post-allogeneic stem cell transplant relapse rates based on the inherited repertoire of KIR genes expressed by donor NK cells, indicating a role for NK cell-mediated suppression of relapse [22,24]. Lastly, NK cells mediate ADCC against myeloma cells in vitro and in vivo, thus enhancing the anti-MM activity of current therapies, which includes mAbs such as the anti-CD38 daratumumab and isatuximab [45] and the anti-SLAMF7 elotuzumab (Figure 2) [70,71].…”
Section: Nkmentioning
confidence: 99%
“…12 Similarly, the addition of elotuzumab to Rd reduced the risk of progression by 30%, with a gain of 4.5 progression-free months compared with the control arm. 14 In this current study, in the lack of a randomized KRd vs. EloRd trial, and with the well-known limitations and susceptibility to the bias of real-life suggestions, 17 we weighed the relative usefulness of one triplet over the other, comparing a multicenter retrospective EloRd cohort 18 with four multicenter retrospective KRd cohorts, [19][20][21][22] all including RRMM cases treated outside of clinical trials. This current clinical practice study's overall results demonstrate that KRd therapy offers a superior outcome than EloRd.…”
Section: Significance Statementmentioning
confidence: 99%
“…The phase 3 ELOQUENT-2 trial was an international, open-label, randomized trial comparing ERd ( n = 321) to Rd alone ( n = 325) in RRMM and showed that the addition of Elo provided an 18% reduction in the risk of death compared to Rd alone [ 51 , 52 ]. In a “real world” experience of ERd in RRMM consisting of a predominantly len naïve population, the regimen was safe with efficacy with a median PFS of 17.6 months and was well tolerated in elderly patients ≥ 75 years of age [ 53 ]. This regimen was FDA approved in 2015 for the treatment of patients with RRMM following two to three prior therapies.…”
Section: Monoclonal Antibodies Are Highly Efficient In the Relapsed Settingmentioning
confidence: 99%